Race and the Religious Contexts of Violence: Linking Religion and White, Black, and Latino Violent Crime - Ulmer, Jeffery T. (2013)
Research has demonstrated that concentrated disadvantage and other measures are strongly associated with aggregate-level rates of violence, including across racial and ethnic groups. Less studied is the impact of cultural factors, including religious contextual measures. The current study addresses several key gaps in prior literature by utilizing race/ethnic-specific arrest data from California, New York, and Texas paired with religious contextual data from the Religious Congregations and Memberships Survey (RCMS). Results suggest that, net of important controls, (1) religious contextual measures have significant crime-reducing associations with violence, (2) these associations are race/ethnic-specific, and (3) religious contextual measures moderate the criminogenic association between disadvantage and violence for Blacks. Implications for future research are discussed.